Insight Into Illness and Psychological Defense Attitudes in People With Chronic Schizophrenia Using Markova's Insight Scale. Issue 12 (December 2021) - Ogawa, Yasuhiro; Fukuhara, Keita; Tanaka, Hiroyuki; Nagata, Yuma; Ishimaru, Daiki; Urakawa, Mizuki; Nishikawa, Takashi
Abstract : Abstract: Insight into illness is a multidimensional phenomenon, and various assessments are available. We focused on Markova's Insight Scale (IS) and investigated the relationship between insight, psychological defenses, and neurocognition in 38 patients with schizophrenia. Results showed that insight was significantly correlated with an immature defense style. Moreover, IS was significantly predicted by immature defense style after adjusting for clinical variables. Although insight is often assumed to be multidetermined with potential contributions from factors such as cognitive function and psychological defensive mechanisms, our results indicated that better insight assessed with the IS is more likely to reflect immature defenses. This may also be reflected in our result that a higher insight score correlated with earlier onset of illness. The insight score may reflect the immature psychological defensive attitudes of schizophrenia and may lead such patients to wish to comply with the views of clinicians.